Shona names: their origins and import. - Viriri, Advice; Nyawo-Shava Viriri, Vongai Z. (Africa Institute for Culture, Peace, Dialogue & Tolerance Studies., 2016)
Contrary to William Shakespeare’s Romeo and Juliet’s notion about a name, according to The Afrocentric experience, [2004], a name is the evidence of one’s existence. A name establishes one’s presence on earth. Names give a person identity and can be a source of pride or shame as it were. From the earliest literature, the Bible, the naming of a people, a place or a person has always been important as an indicator of who that people, place or person would become in the future. Examples of such naming are numerous and include the naming of Jesus, as Emmanuel and Peter as the Rock. In the same breath, in the Shona culture, newly born babies arc given names in the families they are born into.There are traditional criteria followed when giving names. Naming is not done by everybody, elders or the mother and father of the child have the prerogative to name. This article endeavours to analyse the sources and meanings of Shona names given to children. The central thrust of the article is that, in the Shona society, a name has a lot of meaning, and significance and can therefore, even influence the behaviour of the owner.